2000
DOI: 10.1016/s0928-8244(00)00198-x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of a Proteus mirabilis ATF isogenic mutant is not impaired in a mouse model of ascending urinary tract infection

Abstract: Proteus mirabilis, a common cause of urinary tract infection, produces a number of different fimbriae, including ambient temperature fimbriae (ATF). These fimbriae are optimally expressed at 23³C and their contribution to urinary tract infection has so far remained unknown. In the present study, a clinical isolate of P. mirabilis and an isogenic allelic replacement mutant unable to express ATF were tested for their ability to cause infection in the ascending urinary tract infection model in mice. The atf mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 21 publications
6
59
3
Order By: Relevance
“…Several models of UTIs have been described (14,18,19,26,27,34,37,41,49). A number of these studies were conducted to investigate the pathogenesis of various uropathogens and for the evaluation of different antibiotics for UTIs in laboratory animals (2,8,11,12,17,23,33,39,40,43,46).…”
Section: Discussionmentioning
confidence: 99%
“…Several models of UTIs have been described (14,18,19,26,27,34,37,41,49). A number of these studies were conducted to investigate the pathogenesis of various uropathogens and for the evaluation of different antibiotics for UTIs in laboratory animals (2,8,11,12,17,23,33,39,40,43,46).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of S fimbriae and type 1C fimbriae (172,178,340). Uropathogenic P. mirabilis isolates also contain a member of the ␥ 1 -fimbrial clade, the ambient-temperature fimbria (atf) operon; however, the encoded adhesin is not required for cystitis in a mouse model (213,214,373). Gene clusters that are closely related to the ␥ 1 -fimbriae include the lpf operons of S. enterica (28), enterohemorrhagic E. coli (77,334,335), enteropathogenic E. coli (232), and extraintestinal pathogenic E. coli (146).…”
Section: The ␥-Fimbriaementioning
confidence: 99%
“…It was found that NAF/UCA binds the following receptors: asialo-GM 1 , asialo-GM 3 , lactosyl ceramide and galectin (LEE et al 2000, ALTMAN et al 2001. ATF fimbriae are not important in the pathogenicity of human beings (ZUNINO et al 2000). PMP fimbriae were found on canine UTI isolates (BIJLSMA et al 1995), however genes coding this type of fimbriae were found in human clinical isolates (PEARSON et al 2008).…”
Section: Pathogenicitymentioning
confidence: 99%